The Influence of the Problem Based Learning (PBL) Learning Model Assisted by PhET Simulation Media to Increase HOTS of Class 6 Elementary School Students in Electrical Circuits - Hafiza Isbah; Banu Setyo Adi (Postgraduate, University of Mataram, 2024)
The research aims to examine the influence of the PBL Model assisted by PhET Simulation on students' HOTS. The research was carried out at SDN 2 Gantung on class VI students. The sampling technique uses a purposive area sampling method. The research used a quasi-experimental design with data collection techniques through post-tests in the form of multiple choice questions and descriptions, observation, documentation and interviews. The data obtained was analyzed using statistical tests which included normality tests, data analysis using Paired Samples t-Test. Based the validity test, the results show r = 0.81>α (0.05) and the reliability value α> 0.738, the value is valid and reliable. Then results of the normality test value of learning outcomes are 0.416>α (0.05) which exceeds the significant value, so The variable values are normally distributed, followed by using the Paired Samples t-Test, the results of the t-test are learning results at a sig value of 0.00 < α (0.05), then reject H0. So it can be concluded that there is an influence of the Problem Based Learning (PBL) learning model assisted by PhET Simulation on HOTS of 6th grade elementary school students on electrical circuit material.